PELAYANAN PERIZINAN SURAT IZIN USAHA PERDAGANGAN PADA DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU - Harapan Tua R.F.S, Zulmei Akhirisya, Meyzi Heriyanto, (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Licensing Services for Trading Business Licenses at the One-stop Integrated Investment and Services Office. This study aims to determine the licensing services one-stop service permit for the city of Pekanbaru. The research method is qualitative. Research informants were the Head and Secretary of the Pekanbaru DPMPTSP Office, Head of District, community service employees and entrepreneurs. Data collection techniques are interviews and observation. Data analysis through data reduction procedures, data presentation and conclusion drawing. The results showed that the licensing service for issuing permits and extending SIUP permits in Pekanbaru City DPMPTSP can be seen from the attitude of employees who are very responsive in serving the people who come to them, the officers try to know the desires and wishes of service users.